IMPROVING ENTREPRENEURSHIP KNOWLEDGE OF STUDENTS IN MEULABOH STATE VOCATIONAL HIGH SCHOOL 3 WITH LIQUID DISH WASHER SOAP MAKING TRAINING: PENINGKATAN PENGETAHUAN KEWIRAUSAHAAN SISWA DI SEKOLAH MENENGAH KEJURUAN (SMK) NEGERI 3 MEULABOH DENGAN PELATIHAN PEMBUATAN SABUN CUCI PIRING CAIR - Khairun Nisa; Liston Siringo Ringo; Muhammad Reza Aulia; Alfizar; Inayatillah; Eka Kurniasih (WISDOM : Jurnal Pengabdian Kepada Masyarakat Wisdom, 2025)
Liquid dishwashing soap is a liquid solution that contains surfactants that function to remove dirt, grease, and food residue from the surface of eating utensils such as plates, glasses, etc. The need for liquid dishwashing soap is increasing because it is easier to use, cleaner, and more hygienic. Currently, many basic ingredients for making liquid dishwashing soap are sold on the market, so people can make their own so that it is more economical and easier to obtain. This activity aims to improve the entrepreneurial spirit of vocational school students so that they can produce dishwashing soap products and market them through schools so that they can produce independent students after completing their schooling at vocational school by selling the liquid dishwashing soap products to the market or surrounding housewives. The training method for making dish soap products is the Production Based Training (PBT) method, a learning model that emphasizes direct practice and production. In this training, students will use materials and work tools in a simulated environment. This method is also carried out using theory classes, practical demonstrations, and guided exercises. In this training, liquid dishwashing soap was directly made using the necessary ingredients such as Texapon, Email Needle, Natrium Chloride (NaCl), Anti-Bacterial, Perfume Seeds, liquid/powder dye, and Mineral Water. This training process produces approximately 20 liters of liquid dishwashing soap. Apart from that, this dishwashing soap also has quite a large economic value so it can be a solution to improve the community's economy at a lower price compared to the price of factory production which is already sold on the market. This training can provide enthusiasm and stimulate entrepreneurship to vocational high school students.